Adherence to COVID-19 protective behaviours in India from May to December 2020: evidence from a nationally representative longitudinal survey. Issue 2 (1st February 2022) - Schaner, Simone; Theys, Natalie; Angrisani, Marco; Banerjee, Joyita; Khobragade, Pranali Yogiraj; Petrosyan, Sarah; Agarwal, Arunika; Chien, Sandy; Weerman, Bas; Chakrawarty, Avinash; Chatterjee, Prasun; Madaan, Nirupam; et al.
Abstract : Objectives: Since the onset of the COVID-19 pandemic, behavioural interventions to reduce disease transmission have been central to public health policy worldwide. Sustaining individual protective behaviour is especially important in low-income and middle-income settings, where health systems have fewer resources and access to vaccination is limited. This study seeks to assess time trends in COVID-19 protective behaviour in India. Design: Nationally representative, panel-based, longitudinal study. Setting: We conducted a panel survey of Indian households to understand how the adoption of COVID-19 protective behaviours has changed over time. Our data span peaks and valleys of disease transmission over May–December 2020. Participants: Respondents included 3719 adults from 1766 Indian households enrolled in the Harmonised Diagnostic Assessment of Dementia for the Longitudinal Ageing Study in India. Analysis: We used ordinary least squares regression analysis to quantify time trends in protective behaviours. Results: We find a 30.6 percentage point (95% CI (26.7 to 34.5); p<0.01) decline in protective behaviours related to social distancing over the observation period. Mask wearing and handwashing, in contrast, decreased by only 4.3 percentage points (95% CI (0.97 to 7.6); p<0.05) from a high base. Our conclusions are unchanged after adjusting for recorded COVID-19 caseload and nationwide COVID-19 containment policy; we also observe significant declines across socioeconomic strata spanning age, gender, education and urbanicity. Conclusion: We argue that these changes reflect, at least in part, 'COVID-19 fatigue, ' where adherence to social distancing becomes more difficult over time irrespective of the surrounding disease environment.